2019
DOI: 10.1021/acsapm.9b00676
|View full text |Cite
|
Sign up to set email alerts
|

AIE-Active and Thermoresponsive Alternating Polyurethanes of Bile Acid and PEG for Cell Imaging

Abstract: Alternating polyurethanes (PUs) of poly­(ethylene glycol) (PEG) and bile acids were synthesized through a single step condensation and then conjugated with a tetraphenylethene (TPE) derivative, a typical aggregation-induced emission (AIE) molecule, as chain ends. These degradable PUs showed thermo-sensitivity in water, and the phase transition temperatures can be adjusted through varying the ratios of hydrophilicity–hydrophobicity and the concentrations of the polymers. In aqueous solutions, these PUs emitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Similarly, they have also synthesized CA and LCA derived polyurethane-based linear polymer end-locked with tetraphenylethylene (TPE). [59] The BA-based main chain polymer displayed aggregation induced emission (AIE)-and thermo-responsive behavior using 𝛾-cyclodextrin (𝛾-CD) as tuneable activity handle. Apart from pH and inclusion-based CAP crosslinking, the same research group has also reported the photo-crosslinking module of CAPs.…”
Section: Design Trends Of Cholic Acid-based Polymersmentioning
confidence: 99%
“…Similarly, they have also synthesized CA and LCA derived polyurethane-based linear polymer end-locked with tetraphenylethylene (TPE). [59] The BA-based main chain polymer displayed aggregation induced emission (AIE)-and thermo-responsive behavior using 𝛾-cyclodextrin (𝛾-CD) as tuneable activity handle. Apart from pH and inclusion-based CAP crosslinking, the same research group has also reported the photo-crosslinking module of CAPs.…”
Section: Design Trends Of Cholic Acid-based Polymersmentioning
confidence: 99%
“…24,25 Since Tang et al reported the aggregation-induced emission luminogens (AIEgens) in 2001, 26 the unique characteristics of AIEgens have overcome the drawbacks of ACQ, ultimately yielding high levels of fluorescence emission in the aggregated state 27–29 and making modulated fluorescence, with a high fluorescent intensity, possible. Among the AIEgens, especially the most studied tetraphenylethylene (TPE) derivatives, which as a guest could form a stable host–guest complex with γ-CD, 30,31 providing excellent convenience for preparing self-healing hydrogels with AIE behaviors. For example, the host–guest recognition between β-CD and α-bromonaphthalene was successfully incorporated into a supramolecular polymeric hydrogel to realize the emitting phosphorescence.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the phase change process between the gel-sol can be controlled by heating, chemicals, ultrasound, light, electricity, oxidation/reduction, and shear stimulation, etc. [5][6][7][8][9]. These properties mean that such gels exhibit potential applications in sensing [10,11], controlled drug release [12][13][14], removal of toxic dyes [6,[15][16][17], and micro-and nanomaterial preparation [18,19].…”
Section: Introductionmentioning
confidence: 99%